Increasing L2 Learners’ well-being: An EMPATHICS intervention study - Stewart, Glen (Australian journal of applied linguistics (Online), 2023)
This article reports on an intervention related to L2 learner well-being based on Oxford’s (2016) EMPATHICS theoretical framework. The intervention was conducted at a women’s university in Tokyo in three of the researcher’s own first-year, compulsory, four-skills English-language classes. Forty-six learners agreed to take part in the study. To operationalize Oxford’s (2016) framework, the author drew on several areas of the literature, including grit, trait-EI, self-efficacy, L2 motivation, L2 learner autonomy, mindsets, and language-learning strategies. Data collection instruments used consisted of a forty-five item self-assessment tool, a six-item mini-survey to indicate learners’ pre-existing levels of L2 well-being, a self-report homework handout to facilitate learners’ overall reflective process, and an End-of-intervention Evaluation Report. The ten-week intervention consisted of: (1) having the learners self-assess their use of strategy-related tactics in class one and completing the L2 well-being mini-survey; (2) learners providing a written reflection and/or taking action and providing a written report about their actions after class five times across the term related to tactics in the self-assessment with the help of written advice from the researcher; and (3) the researcher providing guidance about multiple tactics in class and having the learners focus on those tactics when completing relevant activities in class. It was hoped that the overall intervention would encourage positive change in learners’ L2 well-being. Practical and theoretical implications are discussed, and avenues for future research are suggested.